2018
DOI: 10.1103/physrevfluids.3.033303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a surface tension gradient on the slip flow along a superhydrophobic air-water interface

Abstract: Superhydrophobic surfaces have been shown to produce significant drag reduction in both laminar and turbulent flows by introducing an apparent slip velocity along an air-water interface trapped within the surface roughness. In the experiments presented within this study, we demonstrate the existence of a surface tension gradient associated with the resultant Marangoni flow along an air-water interface that causes the slip velocity and slip length to be significantly reduced. In this study, the slip velocity al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 49 publications
13
61
0
Order By: Relevance
“…Assuming a strong surfactant, our model predicts that a bulk surfactant concentrationĉ 0 ∼ 10 −13 mM can reduce u I in the same extent and under the same conditions as reported by (27) for both short and long lanes; andĉ 0 ∼ 10 −15 to 10 −14 mM for the experiments reported by (28). Assuming the weak SDS surfactant, our model predictŝ c 0 ∼ 1 to 10 mM (i.e.…”
Section: C2 Limit Of Small Gap Lengthsupporting
confidence: 79%
See 2 more Smart Citations
“…Assuming a strong surfactant, our model predicts that a bulk surfactant concentrationĉ 0 ∼ 10 −13 mM can reduce u I in the same extent and under the same conditions as reported by (27) for both short and long lanes; andĉ 0 ∼ 10 −15 to 10 −14 mM for the experiments reported by (28). Assuming the weak SDS surfactant, our model predictŝ c 0 ∼ 1 to 10 mM (i.e.…”
Section: C2 Limit Of Small Gap Lengthsupporting
confidence: 79%
“…Similarly, (28) report: u I ≈ 8 × 10 −2 for 5 mm long lanes (see their figure 3b), which is significantly reduced compared with the theoretical (surfactant-free) prediction; and u I ≈ 8 × 10 −3 for 15 mm long lanes ( figure 5), which is practically negligible. The main difficulty in applying our theoretical model, for instance to predict the reduced slip velocities measured experimentally by (27) and (28), is that the surfactant properties and their concentrations are completely unknown in their experiments. Instead, we use our model to predict the concentration of surfactant, for three different possible surfactant types, which could lead to the measured u I reported in (27) and (28).…”
Section: C2 Limit Of Small Gap Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…A functional chemical surface has a wide variety of applications including self-cleaning surfaces, drag reduction on ships, and anti-icing technology by repelling supercooled water droplets [1][2][3]. The most effective hydrophobic surfaces found in nature are created using a microstructure, such as that in butterfly wings or the surfaces of lotus plants, and it has been shown that varying the microstructure of such a coating can modify the hydrophobicity of a surface, as well as the wetting properties [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Superhydrophobic materials and surfaces [1][2][3][4] have attracted great interest because of their extreme water-repellent surface property for many potential applications including self-cleaning [5][6][7], hydrodynamic friction reduction [8][9][10], anti-icing [11][12][13][14], anticorrosion [15][16][17][18], biotechnology [19][20][21], thermal systems [22][23][24][25], and micro-and nanodevices [26][27][28]. In particular, previous works on the use of superhydrophobic surfaces as anti-icing coatings have demonstrated that superhydrophobic surfaces have the capability to reduce or even prevent the accumulation and formation of snow and ice on hard solid surfaces [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%